Analysis of the Implementation of the Merdeka Curriculum Function at SMPN 9 Kota Bima - Fahmi, Muhammad Rizal; Adiyan, Fidiatul; Hardiansyah, Hadi; Aulia, Irva (Kopertis Region IV Jabar and Banten, 2025)
The purpose of the study is to analyze the Implementation of the Merdeka Curriculum Function at SMPN 9 Bima City. Research methods, qualitative. Data collection techniques, observation, documentation and interviews. Data collection techniques in research subjects using purposive sampling. Research results, (1) The implementation of the general education function of the curriculum at SMPN 9 Kota Bima can be reflected in the KOSP of SMPN 9 Kota Bima which is designed with the aim of realizing a society that implements the cultural values of Maja Labo Dahu to shape students into individuals who have a nationalistic attitude as provisions to face the development of the times; (2) the implementation of the supplementation function of the curriculum is carried out in a differentiated manner, meaning that the learning process is designed to meet the needs of students; (3) the exploration function is carried out through extracurricular activities, with the aim of exploring the talents possessed by students; (4) the implementation of the expertise function (specialization) at SMPN 9 Kota Bima has not been implemented because it still requires the design and support of facilities and infrastructure as well as experts in the field.